2011
DOI: 10.1016/j.yebeh.2010.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychosocial adjustment in patients with temporal lobe epilepsy using a standard measure

Abstract: Despite the growing evidence of poor psychosocial adjustment, at present there is no formal method of assessment of social adjustment in patients with temporal lobe epilepsy (TLE). First, we assessed social adjustment in patients with TLE using a self-report questionnaire and compared the results with those from quality-of-life (QOL) scales. Second, we verified the influence of cognitive performance and clinical variables of epilepsy on social adjustment and QOL. We evaluated 35 people with TLE and 38 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
3
27
0
1
Order By: Relevance
“…has not yet been determined how many years of seizure-freedom are related to a significant improvement, and the pattern of recovery from epilepsy in terms of social cognitive ability has not Previous evidence has suggested worse psychosocial adjustment in certain epilepsy types such as TLE and mTLE (Gois et al, 2011;Jokeit, 2010). However, Experiment 1 suggested that autistic traits were common to all adults with epilepsy and therefore not exclusive to any single epilepsy type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…has not yet been determined how many years of seizure-freedom are related to a significant improvement, and the pattern of recovery from epilepsy in terms of social cognitive ability has not Previous evidence has suggested worse psychosocial adjustment in certain epilepsy types such as TLE and mTLE (Gois et al, 2011;Jokeit, 2010). However, Experiment 1 suggested that autistic traits were common to all adults with epilepsy and therefore not exclusive to any single epilepsy type.…”
Section: Discussionmentioning
confidence: 99%
“…This is most surprising, given that animal studies have related TLE to functional changes in social behaviours that manifest as ASD, and consistent with such evidence, a number of studies have shown that those with TLE have worse social adjustment (Gois et al, 2011;Marin et al, 2008). On one hand, early onset is a consistent factor for impaired advanced social cognition (Shaw et al, 2004;Hlobil et al, 2008).…”
Section: Social Cognitive Difficulties In Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…In MTLE, the primary brain network involved includes structures of the limbic system, mainly the hippocampus and amygdala that are crucially implicated in learning and memory processes. Epileptogenic foci are most often localized in one brain hemisphere, although epileptogenic medial temporal lesions are bilateral in many cases 1,2 . Neuropsychological assessment of MTLE patients is important to document cognitive impairments in specific domains, such as episodic memory 3,4 and linguistic and nonlinguistic functions 5,6 .…”
Section: Introductionmentioning
confidence: 99%